1986
DOI: 10.1152/ajpregu.1986.251.1.r48
|View full text |Cite
|
Sign up to set email alerts
|

Effect of synthetic atrial natriuretic factor on aldosterone secretion in the rat

Abstract: Direct in vivo measurements of aldosterone secretion were made before and after infusion of synthetic rat atrial natriuretic factor (ANF) into anesthetized rats with markedly different levels of plasma renin activity. Infusion of ANF peptide at 350 ng . kg-1 . min-1 significantly decreased aldosterone secretion by 32% and plasma renin activity by 55% in rats that had been maintained on a normal-sodium diet. Similar reductions in aldosterone secretion and plasma renin activity were observed in hyperreninemic ra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
8
0

Year Published

1987
1987
2013
2013

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(8 citation statements)
references
References 0 publications
0
8
0
Order By: Relevance
“…Atrial natriuretic factor has been found to be a potent in vivo and in vitro inhibitor of aldosterone secretion via a direct effect on the adrenal (Atarashi et al 1984, Burnett et al 1984, Chartier et al 1984, Goodfrield et al 1984, Kudo & Baird 1984, Campbell et al 1985, Espiner et al 1985, Hirata et al 1985, Anderson et al 1986, Higuchi et al 1986, Aguilar 1987, Denker et al 1990, Clark et al 1992) and indirectly through inhibition of remn release (Burnett et al 1984, Maack et al 1984, Kurtz et al 1986, Vari et al 1986). Atrial natriuretic factor also enhances potassium excretion in both animals (Martin et al 1990) and humans (Vesely et al 19946) with the resultant change in the circulating potassium concentration possibly also contributing to the decreased aldosterone secretion that has been observed.…”
Section: Introductionmentioning
confidence: 99%
“…Atrial natriuretic factor has been found to be a potent in vivo and in vitro inhibitor of aldosterone secretion via a direct effect on the adrenal (Atarashi et al 1984, Burnett et al 1984, Chartier et al 1984, Goodfrield et al 1984, Kudo & Baird 1984, Campbell et al 1985, Espiner et al 1985, Hirata et al 1985, Anderson et al 1986, Higuchi et al 1986, Aguilar 1987, Denker et al 1990, Clark et al 1992) and indirectly through inhibition of remn release (Burnett et al 1984, Maack et al 1984, Kurtz et al 1986, Vari et al 1986). Atrial natriuretic factor also enhances potassium excretion in both animals (Martin et al 1990) and humans (Vesely et al 19946) with the resultant change in the circulating potassium concentration possibly also contributing to the decreased aldosterone secretion that has been observed.…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies have dem onstrated that all these atrial peptides do, indeed, signifi cantly enhance Na excretion when infused into healthy human adults [16]. All these atrial peptides have been found to have direct effects on Na metabolism in the kid ney either via opening the Na channel as is the case with ANF [30,31] or via inhibiting the Na+-K+-ATPase as occurs with LANP and VSDL [32,33], In addition to the direct effects on Na metabolism, ANF [7][8][9][10] and LANP [ 17] have indirect effects via decreasing the serum aldo sterone concentrations. Also possibly contributing to the maintenance of serum Na in the normal range is the reported ability of ANF to inhibit vasopressin release [11] Atrial Natriuretic Peptides and Serum Sodium and increase GFR [12], Under physiological conditions, however, these atrial peptides usually do not increase GFR [14,16], Thus, the atrial peptides may be important regulators of Na metabolism via direct and indirect mech anisms outlined above, but their effects on maintaining Na within the normal range in serum does not appear to involve GFR under physiological conditions in healthy individuals.…”
Section: Discussionmentioning
confidence: 98%
“…In addition to diuretic and potent vasodilatorv properties [4,5], atrial natriuretic factor (ANF), consisting of amino acids 99-126 of the ANF prohormone, has natriuretic properties. In pharma cological doses, ANF is known to lower blood pressure and promote salt excretion, and it has been shown that genetic decreases in ANF lead to salt-sensitive hyperten Atrial Natriuretic Peptides and Serum Sodium sion in mice [6], ANF decreases circulating aldosterone concentrations [7][8][9][10], inhibits vasopressin release [11], and has been reported to increase the GFR [12]. Thus, in addition to having direct natriuretic effects [4,5], ANF modulates other factors important in maintaining the Na balance.…”
Section: Introductionmentioning
confidence: 99%
“…Since that time, a wide variety of studies have been performed, and although the conclusions are still controversial, it has been repeatedly shown that at least in the initial stages of both clinical and experimental forms of acute renal failure, plasma renin activity is increased [34,35]. It has also been sug gested that the high level of renin activity causes a reduc tion of GFR by affecting the hydraulic permeability fil tration area coefficient [36], On the other hand, in nor mal animals it has been demonstrated that intravenous infusion of ANF markedly decreased the plasma renin activity, renin secretion rate and plasma aldosterone lev els [37,38]. Based on these observations it is possible that ANF beneficial effects are mediated by an inhibi tion of the renin system.…”
Section: Discussionmentioning
confidence: 99%